The place and role of tourism in the economic development of Serbia - Dimitrovski, Darko; Milutinović, Sonja (Hotel and Tourism Management, 2014)
Tourism as an economic activity is affected by both positive and negative economic and social outcomes of economic and non-economic subjects. Tourism affects not only the redistribution of national income on a global scale, but the redistribution of income between sectors and companies within the national economy as well. The current level of economic development and overall economic efficiency affect the competitiveness of tourism of the Republic of Serbia, and thus determine the place of tourism in the overall economic development. The aim of this paper is to determine the place and role of tourism in the economy of Serbia based on the existing data, and thus propose guidelines for future development.